Project Based Learning for professional identity: A case study of collaborative industry projects in Marketing - Vande Wiele, Philippe; Morris, Darren; Ermine, Jean-Louis (The IIE, 2017)
Assuming that higher educational institutions give credence to the goal of employability of its graduates, the adoption of effective Teaching & Learning methodologies towards such an objective is vital to its purposefulness. Problem Based Learning (PBL) has been proposed as an effective option in this regard, yet the literature is divided around whether this effectiveness carries through in terms of transitioning learners of business degrees into the workplace. This paper outlines a detailed case study describing the Associate Consultant (AC) approach used in the capstone course of an undergraduate Marketing qualification. The AC approach shows that it triggers and develops professional behaviours and self-reflection towards the formation of professional identity (PI) by embedding it in the curriculum through an appropriately benchmarked expectation around engagement and the use of a consulting firm as the overarching context to the PBL capstone course. An address of the whole self, collective dialogue, challenging self-perception, abandonment of performance for grades and high interaction with a real client are found to be highly conducive to PI formation. The findings of this paper strengthen the use of a PBL methodology in capstone business courses and it recommends the AC approach as a viable option to transition learners effectively into the world of work.
Keywords: Higher education; Professional identidy; Employability; Teaching and learning; Self- perception; Professional behaviour; Problem based learning